IMPLIKASI KOMPONEN LAPORAN ARUS KAS, LABA KOTOR, DAN SIZE PERUSAHAAN TERHADAP EXPECTED RETURN SAHAM - Totok Sasongko (University of Merdeka Malang, 2010)
Expected return of an investment was the probabilit y rate dist ribut ion on invest -ment returns. Although investors (stockholders) did not know exact ly what rate of returnthey would get , they had base on their decisions to invest . Work performance measurementused by stockholders in investment decisions were prof it and cash f low. Besides, investorsalso considered company f inancial characterist ic like company size. The main purpose of thisresearch was to analyze the implicat ion of informat ion cash f low statement , gross prof it ,company size toward expected stock return. Populat ion of this research was manufacturecompanies listed at Jakarta Stock Exchange. The sample was selected by purposive sampling.The analysis data used was a mult i linear regression. The result showed that simultaneously,cash f low component , gross prof it and company size had signif icant ef fect to stock expectedreturns. But part ially, the cash f low f rom operat ion and f inancing didnt have signif icantef fect to stock expected returns.